Potential role of poly(A) polymerase in the assembly of polyadenylation-specific RNP complexes. - Terns, M P (1991)
To elucidate the mechanism by which poly(A) polymerase functions in the 3'-end processing of pre-mRNAs, polyadenylation-specific RNP complexes were isolated by sedimentation in sucrose density gradients and the fractions were analyzed for the presence of the enzyme. At early stages of the reaction, the RNP complexes were resolved into distinct peaks which sedimented at approximately 18S and 25S. When reactions were carried out under conditions which support cleavage or polyadenylation, the pre-mRNA was specifically assembled into the larger 25S RNP complexes. Polyclonal antibodies raised against the enzyme purified from a rat hepatoma, which have been shown to inhibit cleavage and polyadenylation (Terns, M., and Jacob, S. T., Mol. Cell. Biol. 9:1435-1444, 1989) also prevented assembly of the 25S polyadenylation-specific RNP complexes. Furthermore, formation of these complexes required the presence of a chromatographic fraction containing poly(A) polymerase. UV cross-linking analysis indicated that the purified enzyme could be readily cross-linked to pre-mRNA but in an apparent sequence-independent manner. Reconstitution studies with the fractionated components showed that formation of the 25S RNP complex required the poly(A) polymerase fraction. Although the enzyme has not been directly localized to the specific complexes, the data presented in this report supports the role of poly(A) polymerase as an essential component of polyadenylation-specific complexes which functions both as a structural and enzymatic constituent.